Biogas Production in Dairy Farming in Indonesia: A Challenge for Sustainability - Jatmiko Wahyudi; Tb. Benito Achmad Kurnani; Joy Clancy (International Journal of Renewable Energy Development, 2015)
Biogas plays an important role in supporting and ensuring the dairy farming sector remains sustainable. Biogas technology is not only as a method to dispose dairy farming waste but also benefiting economically, socially and environmentally. Biogas technology has been introduced since 1970s and many biogas programmes have been implemented in Indonesia. However compare to other countries like China and India, the dissemination of biogas technology in Indonesia runs quite slowly. There are several factors such as financial, policies and people’s perception hindering biogas use regarding the increase of biogas plants installed in Indonesia. In addition, many installed biogas plants are non-functional due to inadequate maintenance causing users stop to operate biogas plants and influencing potential users to reject adopting the technology. This paper provides an overview of biogas production sustainability which consists of five sustainability dimensions: technical, economic, social, environmental and organizational/institutional sustainability. Understanding the biogas sustainability helps stakeholders to realize that in order to promote biogas technology many sectors must be developed and many institutions must be involved and cooperated. The sustainability of biogas will determine the success of biogas dissemination particularly in dairy farming in the future.